1968
DOI: 10.1002/nav.3800150306
|View full text |Cite
|
Sign up to set email alerts
|

The fixed charge problem

Abstract: A fundamental unsolved problem in the programming area is one in which various activities have fixed charges (e.g., set‐up time charges) if operating at a positive level. Properties of a general solution to this type problem are discussed in this paper. Under special circumstances it is shown that a fixed charge problem can be reduced to an ordinary linear programming problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
2

Year Published

1969
1969
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(68 citation statements)
references
References 4 publications
0
66
0
2
Order By: Relevance
“…Hirsch and Dantzig (1968) established that the feasible region of FCTP is a bounded convex set with a concave objective function. An optimal solution occurs at an extreme point of the constraint set, and for a non-degenerate problem with all positive fixed costs, every extreme point of the feasible region is a local minimum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hirsch and Dantzig (1968) established that the feasible region of FCTP is a bounded convex set with a concave objective function. An optimal solution occurs at an extreme point of the constraint set, and for a non-degenerate problem with all positive fixed costs, every extreme point of the feasible region is a local minimum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The observation of Hirsch and Dantzig (1968), which showed that optimal solutions to the fixed-charge problem occur at extreme points, opened a fertile area for developing a class of exact methods. These and other types of exact methods include cutting plane approaches (Rousseau, 1973), vertex ranking strategies (Murty, 1968;McKeown, 1975), and a number of branch and bound approaches with penalty based search tree pruning mechanisms and capacity improvement techniques (Gray, 1971;Kennington, 1976;Kennington and Unger, 1976;Fisk and McKeown, 1979;McKeown and Sinha, 1980;Barr, Glover and Klingman, 1981;McKeown, 1981;Cabot and Erenguc, 1984;and 1986;Schaffer, 1989;McKeown and Ragsdale, 1990;Palekar, Karwan and Zionts, 1990;Lamar and Wallace, 1997;Bell, Lamar and Wallace, 1999;Glover, Amini, and Kochenberger, 2003;and Ortega and Wolsey, 2003).…”
Section: Fc-mip Minimize X O [Fc] = Cx + Fzmentioning
confidence: 99%
“…Wright and Haehling von Lanzenauer (1989) develop a Lagrangian heuristic for the FCTP which is based on relaxing the variable upper bound constraints Xij < Uijyij. It can be proved that an optimal Solution to the FCTP is an extreme point of the convex region defined by constraints (4b)-(4d) (see Hirsch and Dantzig (1968)). Basic feasible solutions to the system (4b)- (4d) define spanning trees of the transportation network.…”
Section: Fixed-charge Transportation Problemmentioning
confidence: 99%